Association Between Vitamin D Level and Neonatal Respiratory Distress Syndrome: A Systematic Review and Meta-Analysis - Zang, Rina; Zhang, Yayu; Zhang, Hanshuo; Zhang, Xueyi; Lv, Yuening; Li, Dan (Frontiers in Pediatrics, 2022)
Background: In recent years, the involvement of vitamin D in the occurrence of lung diseases has gradually become a hot spot. Although the role of vitamin D in normal lung development has been confirmed, the correlation between vitamin D level and neonatal respiratory distress syndrome (NRDS) is not clear. Objective: This study aimed to evaluate the association between vitamin D level and NRDS. Methods: we performed a comprehensive search of the following electronic databases: PubMed, Embase, Cochrane Library, Web of Science and CNKI databases. Literature screening and quality assessment were performed according to inclusion and exclusion criteria. The Newcastle–Ottawa Scale was used to assess the methodological components of each study, and Stata 15.1 software to perform the Meta analysis. Results: A total of 9 case-control studies were included, with 653 infants with NRDS and 501 infants without NRDS. The Meta analysis showed no heterogeneity across all studies( I2=0.0%, P=0.583). The fixed-effect model showed that 25 hydroxy vitamin D level of children in the NRDS group was significantly lower than that of the non-NRDS group(SMD= -0.51, 95%CI: -0.63 to -0.39, p=<0.05). Conclusion: This systematic review and meta-analysis study suggests that vitamin D deficiency is very likely to be a high-risk factor of NRDS, and reasonable vitamin D supplementation during pregnancy and after birth is of great significance.